(untitled) (MAUSAM, 1989)
In this paper, methodologies which were developed at Meteorological pata Utilisation Centre, New Delhi, to compute Quantitative Precipitation Estimates (QPE) and Outgoing Longwave Radiation, (OLR) from INSAT-)B radiance data, are described. QPE computation employs a one-parameter linear model using 3-hourJy INSA T -IB Equivalent Black Body Temperatures (EBBT). The EBBTs are distributed over a 16-class histogram, QPE is computed from the histogram data by calculating fractional cloud cover colder than a chosen threshold temperature and multiplying the same with a regression coefficient. Computations are carried over 2.5° x 2.5° Lat./Long boxes in an area extending from 40° E to 100oE and 35°N to 25° S. OLR is computed, using the mean temperature of the 2.5° Lat./Long box. Monthly mean charts of QPE and OLR are presented for the winter season of 1986 (December 1986 to February 1987). Low values of OLR coincide well With the raining areas. The isopleth "of 240 watts/m2 is found to delineate the raining area. Daily computation of OLR and QPE were also carried out during the life period of a severe cyclonic storm in the Bay of Bengal during January-February 1987. Areas of heavy rain and low OLR are in agreement. Finally, INSA T OLR values are compared with those of NOAA. While the pattern correlation between them is .85, OLR values of NOAA are found to be higher in the warmer areas.